Strategies to Promote Autonomy and Self-Directed Learning in the Classroom (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article explores the pivotal focus on learner autonomy and self-directed learning in language education. It highlights the shift from traditional teacher-centric approaches, emphasizing collaborative and student-centered methods. Strategies such as goal setting, learning contracts, project-based learning, and technology integration are discussed to promote autonomy. The article acknowledges challenges and emphasizes the importance of balancing guidance and autonomy. Ultimately, empowering students to lead their learning prepares them for a rapidly changing world.